Effects of Climate Change on Weeds and Invasive Alien Plants in Sri Lankan Agro-Ecosystems: Policy and Management Implications - Buddhi Marambe; Siril Wijesundara (Frontiers in Agronomy, 2021)
Changes in the climate have worsen the problems caused by weeds and invasive alien plants (IAPs) in agro-ecosystems at global scale resulting from their changes in the range and population densities. Over the past six decades, Sri Lanka has experienced a slow but steady increase in annual environmental temperature by 0.01–0.03°C. Increasing extreme events of rainfall, wetter wet seasons, and drier dry seasons are some of the characteristic features of the changes in the climate observed in Sri Lanka over the years. The Ministry of Environment (MOE) in Sri Lanka has established a National Invasive Species Specialist Group (NISSG) in 2012 and adopted the National Policy on Invasive Alien Species (IAS) in Sri Lanka, Strategies and Action Plan in 2016. Further, the MOE has developed and adopted protocols to assess the risk of IAS at pre- and post-entry level to the country while incorporating climate change concerns. Periodic risk assessments have being carried out to prioritize actions against IAS in Sri Lanka. The Ministry of Agriculture as adopted a National Weed Strategy (NWS) and has identified the Weeds of National Significance (WONS) under different priority crops. A study done in 2014 has clearly shown that weed control costs in agricultural lands in several district of Sri Lanka were nearly doubled during the years that experienced El Niño Southern Oscillation (ENSO). Further, studies have clearly indicated that IAPs also survive, expand and impact the continuously disturbed environments in agro-ecosystems. Panicum trichocladum, a species listed as a potential invasive based on the risk assessment done in 2016, has shown an increase in its population density and distribution in Sri Lanka during the last 2–3 years. However, weeds and IAPs in agro-ecosystems have drawn less attention of policy makers, scientists, and practitioners in relation to impact of climate change in island ecosystems. This paper focuses on the scientific evidence reported in agro-ecosystems in Sri Lanka on climate-related impacts on agriculturally important weeds and IAPs, and the efforts made to manage their introduction and spread across the country.